Chemistry in eriocaulaceae - Dokkedal, Anne Lígia [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Sano, Paulo Takeo; Vilegas, Wagner [UNESP] (My University, 2008)
Eriocaulaceae is a pantropical family that comprises about 1100 species distributed in 11 genera. The infrafamilial relationships are still unsatisfactorily resolved, because of the tiny flowers and generalized morphology, which makes the taxonomy very difficult. Flavonoid and naphthopyranone profiles have proved to be important in order to contribute to the alignment of genera into the family. We here present a survey of the chemical data of Eriocaulaceae with a discussion about their contribution to the taxonomy of Eriocaulaceae. © 2008 Verlag der Zeitschrift für Naturforschung.
Keywords: Chemotaxonomy; Eriocaulaceae; Flavonoids; flavone derivative; flavonoid; xanthone; xanthone derivative; chemical structure; chemistry; classification; conformation; isolation and purification; structure activity relation; Flavones; Models, Molecular; Molecular Conformation; Structure-Activity Relationship; Xanthones